Chitosan-PVA-poly chloroaniline blended with C 30B for mechanical, electrical and optical properties - DILLIP KUMAR BEHERA; KAMPAL MISHRA; P.L.NAYAK (International Journal of Pharma and Bio Sciences, 2017)
Chitosan has received great attention of the researchers from different fields throughout the World because of its unique properties and characcteristics. On the other hand polyvinyl alcohol has applications in various fields, from packaging industries to biomedical field. There are enormous work has been done on conducting polymers using Polychloroaniline. But a very limited reports are available on the synthesis of conducting polymers by blending Chitosan-Polychloroaniline and PVA-Polychloroaniline along with organically modified MMT i.e. C30B. In this research programme Chitosan (CS)-Polyvinyl alcohol (PVA)/Polychloroaniline (PClAn) altogether were blended with C 30B for the preparation of polymer nanocomposites where the aniline monomer is allowed to polymerize in presence of HCl. Then polymer nanocomposites were characterized by various techniques like FT-IR, X-ray diffraction, and TGA. The Electrical conductivity of the nanocomposites were also measured. FTIR analysis provided an evidence for the formation of nanocomposites. X-ray diffraction analysis confirmed that the clay was intercalated in between the polymer matrix. A delayed onset of thermal degradation by as much as 70 °C in case of CS-PVA /PClAn/C 30B indicates that the incorporation of C 30B increased the thermal stability of the polymer.